Cesarean Scar Ectopic Pregnancy: The Lurking Danger in Post Cesarean Failed Medical Abortion - Monika Anant; Anita Paswan; Chandra Jyoti (Tehran University of Medical Sciences, 2020)
Cesarean scar pregnancy (CSP) is a potentially life threatening ectopic pregnancy where a missed diagnosis is commoner than an accurate diagnosis. Incidence of Ectopic pregnancy is 1 - 2 % and cesarean scar ectopic occurs in about (0.05%) 1 in 2000 of all pregnancies. With increasing cesarean section rates worldwide, CSP is bound to increase with its dreaded complications like uterine rupture and catastrophic hemorrhage. Three patients misdiagnosed as incomplete miscarriages in post cesarean pregnancies in other centers were found to be CSP in Gynaecology department of a tertiary level hospital. All three patients were managed successfully, two surgically and one medically.